6th International Symposium on Tonal Aspects of Languages (TAL 2018) 2018
DOI: 10.21437/tal.2018-7
|View full text |Cite
|
Sign up to set email alerts
|

Tonal Hybridization in Yami-Mandarin Contact

Abstract: Yami, an endangered Austronesian language spoken on Orchid Island in Taiwan has been under heavy influence from Mandarin for several decades. In the current linguistic ecology, the pressure of Mandarin on Yami is increasing and its influence has been reported in Yami intonation. This study, on the flip side, examines whether Yami influence has also diffused through the Mandarin spoken on Orchid Island. Taiwan Mandarin speakers make a three-way distinction in sentence intonation: (1) falling statements, (2) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Mandarin speakers use the subject–verb–object (SVO) order and a falling intonation in declarative sentences ( Chuang et al, 2007 ; Chuang & Fon, 2016 ; Lai, 2018a , 2019 ; Lai & Gooden, 2018c ; Shen, 1990 ). Yes/no questions and declaratives have identical syntactic structures and the most widely used types of questions include as follows:…”
Section: Intonation In Mandarin and Yamimentioning
confidence: 99%
See 1 more Smart Citation
“…Mandarin speakers use the subject–verb–object (SVO) order and a falling intonation in declarative sentences ( Chuang et al, 2007 ; Chuang & Fon, 2016 ; Lai, 2018a , 2019 ; Lai & Gooden, 2018c ; Shen, 1990 ). Yes/no questions and declaratives have identical syntactic structures and the most widely used types of questions include as follows:…”
Section: Intonation In Mandarin and Yamimentioning
confidence: 99%
“…A comparison between Mandarin and Yami question intonation is shown in Table 2 , among which NQ, DQ1, and DQ2 are the focus of this paper. Schematic representations of Mandarin intonation are plotted based on previous research ( Chuang et al, 2007 ; Chuang & Fon, 2016 ; Lai, 2018a , 2019 ; Lai & Gooden, 2018c ; Lee, 2005 ; Liing, 2014 ; Shen, 1990 ). For the Yami data, given that these are (semi-)spontaneous speech with variable morphosyntactic structure, it is unsurprising that participants produced different variants of the same utterance.…”
Section: Intonation In Mandarin and Yamimentioning
confidence: 99%
“…Therefore, there must be non-F0 cues in the speech signal that can compensate for the absence of F0 in whispered tone recognition (Jiao & Xu, 2019). Some researchers proposed some secondary cues, such as duration (Gao, 2002;Li & Guo, 2012;Li & Rong, 2012;Liu & Samuel, 2004;Yang et al, 2005), intensity contour (Gao, 2002;Li & Guo, 2012), and formant frequency (Eklund & Traunmüller, 1997;Higashikawa et al, 1996;Kallail & Emanuel, 1984;Matsuda & Kasuya, 1999), that were exaggerated by the speakers to the needs of the listeners. For example, the duration of tones in whispered speech was much longer than that in phonated speech (Li & Guo, 2012;Li & Rong, 2012;Yang et al, 2005), and the duration differences across the four lexical tones were exaggerated in whispered Mandarin (Li & Guo, 2012).…”
Section: Perception Of Lexical Tones In Whispered Speechmentioning
confidence: 99%
“…Some researchers proposed some secondary cues, such as duration (Gao, 2002;Li & Guo, 2012;Li & Rong, 2012;Liu & Samuel, 2004;Yang et al, 2005), intensity contour (Gao, 2002;Li & Guo, 2012), and formant frequency (Eklund & Traunmüller, 1997;Higashikawa et al, 1996;Kallail & Emanuel, 1984;Matsuda & Kasuya, 1999), that were exaggerated by the speakers to the needs of the listeners. For example, the duration of tones in whispered speech was much longer than that in phonated speech (Li & Guo, 2012;Li & Rong, 2012;Yang et al, 2005), and the duration differences across the four lexical tones were exaggerated in whispered Mandarin (Li & Guo, 2012). With regard to the intensity contour, compared with phonated speech, Gao (2002) found that speakers exaggerated the intensity contour when they were whispering, and concluded that intensity contour played a crucial role in whispered tone perception especially for Tone 3 and Tone 4.…”
Section: Perception Of Lexical Tones In Whispered Speechmentioning
confidence: 99%
“…While these rubrics make no direct predictions for higher levels of prosody, there is a growing body of research showing that higher level prosody is in fact permeable under contact. Yami has revealed signs of contactinduced segmental [4,5] and prosodic variation [6].…”
Section: Introductionmentioning
confidence: 99%